DMS2015-26: Pupils׳ collaboration around a large display. (December 2015) - Lanzilotti, R.; Ardito, C.; Costabile, M.F.; De Angeli, A.; Desolda, G.
Abstract: Collaboration is acknowledged as a key element of learning. Thus, it is valuable to develop Information and Communication Technology applications that, implemented on proper devices, can support collaborative learning. Large multi-touch displays appear to encourage collaboration by offering users a shared environment to act upon. However, little knowledge is available on the actual influence of this technology on human behavior and more empirical evidence is needed to better understand its capability to foster collaboration. This paper provides a contribution in this direction by presenting a field study that helps understand collaborative practices of pupils playing an educational game that runs on a multi-touch large display. This study involved 98 fifth-graders at a primary school (average age 10 years old). Results confirmed the potential of large displays as useful devices for collaborative learning.